68.2: Invited Paper: Development of Novel Optical Bonding Process and Materials for Flat Panel Display Modules. Issue 1 (1st July 2013) - Shinya, Yoshihisa; Hayashi, Kozaburo; Ogawa, Koichi; Kamiyay, Kenji; Toyoda, Tomoyuki; Hayashi, Naoki
Abstract: We have developed Hybrid SVR™, an optical elasticity UV curable resin that improves the contrast and shock resistance of flat panel display (FPD) modules. The unique bonding process used for Hybrid SVR™ offers a number of advantages. The resin coating on the cover glass can be transformed into a pressure sensitive adhesive by irradiating it with UV light. The cover glass can then be bonded with the FPD module. This method significantly improves the process margin, which results in an overflow‐free boundary and easier thickness control. In addition, the reduced cure shrinkage results in less stress being applied to the FPD module.